Increasing Of Using Picture In Teaching Comparison Degrees - Fitri Ningsi (JURNAL PENDIDIKAN BAHASA, 2017)
Objective of this research is to know the influence of using picture in teaching comparison degrees. The research design is experimental. In this research the population was the eleventh grade of SMAN I Monta in academic year 2017/2018 which consist of 144 Students from 4 classes.In this study, the writer used cluster random sampling technique to take the sample, the writer was taken two small piece of paper. The small piece of paper is roll and mixed. Then, without prejudice the writer take two small piece of paper, they are the first taken was class MIP A 3 34 students as the experimental class and the second taken MIPA 4 34 as the control class. The instrumen for this research is test. Based on the analysis data,he result showed that the null hypothesis is rejected and alternative hypothesis is clearly accepted. So, the picture has positive influence in teaching comparison degrees.